Aksi Pornoaksi Menjadi Bukti Forensik Dari Kejahatan Tindak Asusila - Dimas Maulana Nugroho; Yunan Prasetyo Kurniawan (Publikasi Indonesia, 2025)
The problem that is currently a case concerns an action that violates norms in the form of an immoral act where this action is currently being talked about and is shocking the public, especially the cyber community because this case has become a big highlight, especially since this immoral act has already led to the law because there is already a law. -Pornography laws in the current modern era, immoral acts are not something new because there have been many incidents related to immoral acts. Several incidents have recently gone viral, such as what happened in Bandar Lampung City, there was a student from a well-known state university. in Lampung committed a pornographic act when carrying out a transaction at the cashier by showing his genitals in front of the cashier of one of the mini supermarkets. Based on the information that the author obtained, the action carried out by the perpetrator has been carried out frequently it has even been repeated more than once, so from the case that has been described, the author will use several methods. In writing this journal, it is a qualitative method to see the facts of the case of immoral acts from forensic evidence which has become strong evidence in the form of recorded videos that are happening and the nature of writing this journal is normative juridical in the form of laws related to this case. Art 181 of the Criminal Code which regulates obscenity and uses Law No. 44 of 2008 regarding pornography as strengthening strong evidence of immoral acts committed by the perpetrator and uses the Information and Electronic Transactions Law Number 1 of 2024 as the basis for video evidence in the investigation video recording that proves the perpetrator committed an immoral act.